Hubungan Komponen Health Belief Model (Hbm) Dengan Kepatuhan Minum Obat dan Tingkat Stress pada Pasien Hipertensi - Amir Hamzah (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2024)
The health belief model (HBM) is a model used to describe individual beliefs in healthy living behaviors so that individuals will perform healthy behaviors, which can be in the form of preventive behaviors or the use of health facilities. The purpose of this study is to determine the relationship between the components of the health belief model (HBM) with medication adherence and stress levels in hypertensive patients. This study uses an observational analytical method with a cross-sectional design. The sample used was 90 people, the criteria for nurse respondents working in the COVID-19 isolation room, still registered as active and not on leave, and having physical and psychological health conditions. The data collection tool uses questionnaires, namely the Health Belief Model (HBM), medication adherence and stress levels. Data analysis techniques of chi-square test and multiple logistic regression. The results of this study found that there was a relationship between the Health Belief Model (HBM) and medication adherence (p = 0.000) and stress levels (p = 0.002) in hypertensive patients. The results of the Multiple Logistic Regression Test can be found that Age, Gender, Education, and Health Belief Model (HBM) have a relationship with Drug Adherence in Hypertensive Patients. For hypertensive patients, it is recommended to be able to pay attention to their lifestyle, for example, related to adhering to medication, reducing the consumption of sugar, salt, and carbohydrates, eating fruits and vegetables, managing stress levels, exercising, staying away from cigarette smoke and not drinking alcohol so that it can reduce hypertension complications and improve the quality of life.